Outcomes and analysis of fetomaternal elements and delivery strategies with neonatal respiratory distress - ., Sambedna; Kumar, Amit; Chakore, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Perinatal asphyxia is one of the most important causes of morbidity and mortality in neonates. Perinatal asphyxia occurs in association with different maternal and fetal determinants. However, the relation of associated factors with perinatal asphyxia is not well studied. The aim of this study was to determine the association of maternofetal factors and mode of delivery with perinatal asphyxia in a tertiary care centre. Methods: This was a retrospective comparative study conducted in department of OBG in tertiary care health centre. A total 200 newborns were selected for study out of which100 newborns were with asphyxia at birth as study group and 100 non asphyxiated newborns were taken as control group. Maternal factor like age, parity, gestational age and fetal factor like weight at birth and mode of delivery were studied to established association on perinatal asphyxia. Results: Maternal factor like age, parity, gestational age had not significant relationship with perinatal asphyxia. Maximum number of babies delivered in both control and the study group were in the range of 2.6 to 3kg.In this study birth weight did not have significant relationship with perinatal asphyxia. Proportions of LSCS was comparatively higher in the study group though. The delivery mode did not have any statistically significant influence on the newborns affliction with birth asphyxia (p>0.05). Conclusions: Findings of this study highlight the need for the better obstetrical care and awareness of the possible presence of the risk factors of PNA (perinatal asphyxia) among mothers and fetus, so that the incidence and complications of PNA could be prevented or at least appropriately managed. It can reduce the high incidence of morbidity and mortality due to birth asphyxia.